Monte-Carlo simulations of the radiative recombination of ions with electrons in cold magnetized plasma - Banaś, Dariusz; Jagodziński, P.; Pajek, M.; Gumberidze, Alexandre; Surzhykov, Andrey; Stöhlker, Thomas (Physica scripta, 2014)
We report here on the results of Monte-Carlo simulations of the radiative recombination of highly charged ions with low-energy electrons in the presence of a guiding magnetic field. The simulations are based on a semi-classical geometrical model, recently proposed by our group, which has been developed in order to explain systematic discrepancies, the so-called ‘enhancement effect’, of the radiative recombination rates measured in the guiding magnetic field of electron coolers with respect to theoretical calculations. With the simulations, we demonstrate that the enhancement of radiative recombination rates in the magnetic field could be caused by ‘transverse’ collisions with the impact parameter in the μm range and the impact parameter cut-off value depending on the strength of the guiding B-field in magnetized plasma. In this paper, the methodology of the simulations, the obtained B-field dependence of the radiative recombination enhancement and the observed impact parameter cut-off will be discussed.
Gesehen am 25.08.2020